Impact of nutritional intervention on the cardiovascular health of elderly people in low-income communities: An experience in the Galo I Family Health Strategy, Belém – Pará (Research, Society and Development, 2024)
Objective: To evaluate the impacts of a nutritional intervention aimed at the elderly on lifestyle and chronic and cardiovascular disease control in a context of financial limitation. Method: This report documents a qualitative and descriptive investigation, aimed at ascertaining the effects of nutritional strategies on the cardiovascular health of elderly individuals in economic vulnerability who are served by the Family Health Strategy, in a neighborhood in Belém-Pará. This study was conducted in accordance with the ethical precepts of research with human beings, respecting their autonomy, privacy, and confidentiality.  Results: The nutritional intervention in the Family Health Strategy Galo I showed preliminary improvements in glycemic control and blood pressure in the elderly, with an increase in adherence to nutritional guidelines and medical treatment. The application of the Framingham Score indicated a moderate to high risk of cardiovascular diseases. Economic challenges persist, demanding adaptations in dietary recommendations to be accessible and effective. Conclusion: It is concluded that it is essential that public policies be developed and implemented to ensure that the elderly in low-income communities have better access to healthy foods and integrated health care.